Hydroclimate reconstruction in central Japan over the past four centuries from tree-ring cellulose δ18O. (7th October 2017) - Sakashita, Wataru; Miyahara, Hiroko; Yokoyama, Yusuke; Aze, Takahiro; Nakatsuka, Takeshi; Hoshino, Yasuharu; Ohyama, Motonari; Yonenobu, Hitoshi; Takemura, Keiji
Abstract: The East Asian summer monsoon is an important part of the Earth's climate system that is characterized by variations in the strength and expansion of the summer rain band. Rainfall reconstructions in China have revealed changing patterns of rainfall during the Little Ice Age (LIA), but limited hydroclimate reconstruction around Japan have hindered detailed understanding of physical processes associated with the atmospheric system in the western North Pacific. Here, we report relative humidity variations in the Meiyu/Baiu season from 1600–1959 CE by using tree-ring cellulose oxygen isotopes from central Japan; this is the first record of the LIA from the easternmost regions of the East Asian monsoon domain. Our data suggest that the wettest period occurred around 1780–1880 CE corresponding to the final stage of the LIA. This shift was concurrent with sea surface temperature negative (positive) anomalies around the Philippines (off eastern Japan). We suggest that meridional atmospheric circulation was weak during the last stage of the LIA.